TEKNIK LINKING DALAM PEMBACAAN BERITA TELEVISI VOICE OF AMERICA: Studi Pembelajaran Kreatif pada Mata Kuliah Bahasa Inggris Program Studi Televisi dan Film FSRD Institut Seni Indonesia Surakarta - Kurniawan, Donie Fadjar (Capture : Jurnal Seni Media Rekam, 2011)
The focus of the research is to explore creativity in the application of linking techniquesto improve English fluency in order to increase the understanding of the English languagethrough the medium of television news. The method used is a combination betweendemonstrations and simulations method, based on experiences through reading andlistening skills. Simultaneously both these skills are applied in the instructional processin the classroom by using English-language news items from Voice of America SpecialEducation Report. The result of this study is that technique of linking is found in theEnglish News presented in television. Linking technique was applied to the type ofconsonant-vowel as well as the vowel-vowel. Consonant-vowel found in more thanthe vowel-vowel. The more linking technique found the more it makes a rapid speechin the case of presenting English news. By knowing the characteristics of the applicationof the technique linking, it is expected that Indonesian audience in general and studentof television study program in particular can understand the news more easily.